The White Wedding: Affect and Economy in South Africa in the Early Twentieth Century. (18th August 2014) - Erlank, Natasha
Abstract: Discussions of church weddings are not standard in accounts of African marriage in South Africa in the early twentieth century. However, from the 1890s onward, church weddings were becoming more common, and by the 1930s more Africans married in church than elsewhere. Indeed, these wedding ceremonies provide insight into how black families experienced and created their own social status in a context in which white South Africans viewed black weddings as a symbol of racial misappropriation. Via weddings and their associated commodification, families held on to and proclaimed the value of family life, and importantly, broader social networks as well as status-based associational life in an era of familial disintegration. At the same time weddings were often a double-edged indicator of status through their reference to sexual purity by means of white frocks. Résumé: Les discussions sur les mariages religieux ne sont pas standard dans les comptes-rendus de mariages africains en Afrique du Sud au début du XXe siècle. Cependant, depuis les années 1890, les mariages religieux sont de plus en plus communs, et depuis les années 1930 plus d'Africains se sont mariés à l'église qu'ailleurs. En effet, ces cérémonies de mariage donnent un aperçu de la façon dont les familles noires ont connu et ont créé leur propre statut social dans un contexte dans lequel les Sud-Africains blancs considéraient les mariages entre noirs comme un symbole de misappropriation raciale. Via ces mariages et leur consommation associée, les familles perpétuaient leurs valeurs sur la vie de de famille, ainsi que les réseaux sociaux plus larges et la vie associative fondée sur un statut dans une ère de désintégration familiale. En même temps ces mariages étaient souvent un indicateur à double tranchant à travers leur référence à la pureté sexuelle par le biais du port de robes blanches.